East African HIV care: depression and HIV outcomes. (31st May 2019) - Meffert, S. M.; Neylan, T. C.; McCulloch, C. E.; Maganga, L.; Adamu, Y.; Kiweewa, F.; Maswai, J.; Owuoth, J.; Polyak, C. S.; Ake, J. A.; Valcour, V. G.
Abstract : Importance: Depression is a common co-morbidity for people living with HIV (PLWH) and is associated with elevated plasma HIV RNA levels. While depression correlates with deficits in antiretroviral (ARV) adherence, little data exist to inform the relationship between depression and HIV vial load more broadly. Objective: To examine the relationship between depression and viral load in the African Cohort Study (AFRICOS) independently of ARV adherence. Design: PLWH in Kenya, Uganda and Tanzania underwent screening for depression using the Center for Epidemiologic Studies Depression Scale (CESD) upon enrollment at AFRICOS HIV care sites. Setting: AFRICOS is an ongoing prospective longitudinal cohort study enrolling HIV-infected adults at HIV care centers including sites in Kenya, Tanzania and Uganda. These sites are administered by President's Emergency Plan For AIDS Relief programs. Participants: HIV+ individuals were eligible if they were at least 18 years old, receiving HIV care at the enrolling clinic and consented to data and specimen collection. Main outcome measure: CESD. Results: Among 2307 participants, 18–25% met the CESD threshold for depression. Depression was associated with decreased ARV adherence (OR 0.59, p  =  0.01). Higher scores on three CESD items were significantly associated with 209–282% higher viral load, independently of ARV adherence among participants on ARVs ⩾6 months. Conclusions: PLWH had high prevalence of depression on the CESD. Diverse depression symptoms were independently associated with increases in viral load, underscoring the need for comprehensive treatment of depression.